Framing Strategies and User Engagement in Digital Health Advocacy: A Case Study of the #WorldMentalHealthDay Campaign on Instagram Reels - Siti Nur Ashiqqin Mohd Asha'ari; Kartini Kamaruzzaman (Al-i’lam - Journal of Contemporary Islamic Communication and Media, 2026)
The framing strategies and user engagement within digital health advocacy are examined through a case study of the #WorldMentalHealthDay campaign on Instagram. Adopting a qualitative case study methodology, the research employs content analysis to evaluate five high-engagement Instagram Reels. This is followed by a thematic analysis of systematically sampled user comments to examine how audiences interpret and engage with these digital narratives. Grounded in Framing Theory, the investigation explores the alignment between strategic message construction and user engagement. The findings indicate that content creators significantly utilize moral evaluation and problem definition to normalize mental health struggles and reduce social stigma. Messages frequently emphasize affirming individual self-worth and reframing recovery as a valuable, non-linear process. User responses largely reflect high levels of emotional resonance, characterized by peer support and shared vulnerability. The analysis suggests that for this campaign, the analyzed Reels functioned primarily as a communal, affective space for solidarity rather than as a source for technical health information. Ultimately, the research underscores the critical importance of strategic framing in digital mental health initiatives. It highlights the campaign's potential to foster empathy and catalyze public engagement, while suggesting a need for a more balanced integration of emotional validation and actionable health resources in future digital advocacy.